KONSEP JUAL BELI DALAM FATWA DSN-MUI - Fathoni, Nur (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2013)
There are several fatwas issued about buying and selling is not sequentially and respectively describes their own subject matter. As a result of modern Islamic legal thought, DSN-MUI fatwa interesting to study inductively to find a linkage study of classical fiqh with the provisions of the banking system and mechanism in these fatwas . The problems studied in this paper is the concept of buying and selling in the DSN-MUI fatwa is How it relates to the system of fiqh and Shariah banking mechanism in DSN-MUI fatwa? This study is the research literature by using a qualitative approach. The study found a link between the data and the system of fiqh with the provisions of Shariah banking mechanism DSN-MUI fatwa about buying and selling. The concept of buying and selling in the DSN-MUI fatwa designed to avoid gharar, riba by changing procedures and financing dhalim be based iwadh item form, not a loan (qardh), set the selling price as the final price that can not be combined with any cause, but can reduced on the basis of LKS policy. Late fee of rich clie not being able to shariah bank. In buying and selling foreign exchange should require cash, as opposed to buying and selling goods that is designed to delay installments. The results of the Islamic legal thought DSN-MUI fatwa about buying and selling successfully avoid formalistic forms of riba, gharar and dhalim, but have not managed to uphold the moral essence in buying and selling. Morality and law are still separate in their each areas.